Fatty acid-binding protein 4 is an independent factor in the pathogenesis of retinal vein occlusion. - Fumihito Hikage; Masato Furuhashi; Yosuke Ida; Hiroshi Ohguro; Megumi Watanabe; Soma Suzuki; Kaku Itoh (PLoS ONE)
The main objective of current study was to identify the fatty acid-binding protein 4 (FABP4) expressed in both adipocytes and macrophages in vitreous fluid from patients with retinal vein occlusion (RVO). Patients with RVO (n = 14, CRVO; central RVO n = 5, BRVO; branch RVO n = 9) and non-RVO (macular hole or epiretinal membrane, n = 18) were surgically treated by a 25 or 27G vitrectomy. Undiluted vitreous fluid samples obtained as the result of surgery were subjected to enzyme-linked immunosorbent assays to measure the levels of FABP4 and vascular endothelial growth factor A (VEGFA).Data including ocular blood flow by laser speckle flow graphy (LSFG), height and weight, systemic blood pressures and several blood biochemistry values were collected. Among the LSFG mean blur rate (MBR) values of the optic nerve head (ONH) at baseline, MA (MBR of all area), MV (MBR of the vascular area), and MV-MT (MBR of the tissue area) were significantly decreased in patients with CRVO. The levels of V-FABP4 and V-VEGFA were relatively or significantly (P< 0.05) higher in the BRVO or CRVO patients compared to the non-RVO patients, respectively. A positive correlation (r = 0.36, P = 0.045) or a negative correlation (r = -0.51, P = 0.006) was observed between Log V-FABP4 and Log V-VEGF, or Log V-FABP4 and MV-MT at post-operative 1-week, respectively. Furthermore, neither of these factors were affected with respect to sex, body mass index and several clinical parameters that were collected, except that a positive correlation was observed for Log V-FABP4 with blood urea nitrogen. Stepwise multivariable regression analyses indicated that MV-MT at post-operative 1week was independently associated with Log V-FABP4 after adjustment for age and gender, and gender and Log V-FABP4 were independently associated with Log V-VEGFA after adjustment for age. The findings reported herein suggest that an independent factor, FABP4 may be synergistically involved in the pathogenesis of RVO with VEGFA.